Unearthing inter-job dependencies for better cluster scheduling - Chung, Andrew; Krishnan, Subru; Karanasos, Konstantinos; Curino, Carlo; Ganger, Gregory R. (Symposium on Operating Systems Design and Implementation (OSDI), 2020)
Inter-job dependencies pervade shared data analytics infrastructures (so-called "data lakes"), as jobs read output files written by previous jobs, yet are often invisible to current cluster schedulers. Jobs are submitted one-by-one, without indicating dependencies, and the scheduler considers them independently based on priority, fairness, etc. This paper analyzes hidden inter-job dependencies in a 50k+ node analytics cluster at Microsoft, based on job and data provenance logs, finding that nearly 80% of all jobs depend on at least one other job. Yet, even in a business-critical setting, we see jobs that fail because they depend on not-yet-completed jobs, jobs that depend on jobs of lower priority, and other difficulties with hidden inter-job dependencies. The Wing dependency profiler analyzes job and data provenance logs to find hidden inter-job dependencies, characterizes them, and provides improved guidance to a cluster scheduler. Specifically, for the 68% of jobs (in the analyzed data lake) that exhibit their dependencies in a recurring fashion, Wing predicts the impact of a pending job on subsequent jobs and user downloads, and uses that information to refine valuation of that job by the scheduler. In simulations driven by real job logs, we find that a traditional YARN scheduler that uses Wing-provided valuations in place of user-specified priorities extracts more value (in terms of successful dependent jobs and user downloads) from a heavily-loaded cluster. By relying completely on Wing for guidance, YARN can achieve nearly 100% of value at constrained cluster capacities, almost 2x that achieved by using the user-provided job priorities.